CODE SWITCHING IN EFL CLASSROOMS: FUNCTIONS, FREQUENCY, AND TEACHER ATTITUDES IN THE UZBEKISTAN CONTEXT (Ustozlar uchun, 2026)
Code-switching — the alternating use of two or more languages within a single communicative context — is a widely observed phenomenon in multilingual EFL classrooms. This study investigates the functions, frequency, and pedagogical implications of code-switching (CS) between Uzbek, Russian, and English in university-level EFL classrooms in Uzbekistan. Employing a convergent mixed-methods design, data were collected through video-recorded classroom observations (20 sessions), structured teacher interviews (n=15), and a learner attitude questionnaire (n=120). Findings indicate that code-switching served five primary functions: translation, clarification, classroom management, metalinguistic discussion, and affective support. Teacher-initiated CS was significantly more frequent (68%) than learner-initiated CS (32%). While most teachers acknowledged CS as sometimes pedagogically necessary, over half reported feeling conflicted about its use, fearing it might reduce students' English exposure. Learners, however, generally held positive attitudes toward moderate CS, citing it as a source of comprehension and emotional comfort. The study argues for a principled, deliberate approach to code-switching as a legitimate pedagogical tool in the Uzbek multilingual EFL context.